2011
DOI: 10.3892/ijo.2011.1189
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a potent epigenetic biomarker for resistance to camptothecin and poor outcome to irinotecan-based chemotherapy in colon cancer

Abstract: Abstract. Drug resistance remains a major obstacle to successful cancer treatment. Genome-wide comprehensive analysis identified a novel gene, glucocorticoid-induced protein-coding gene (DEXI), which was frequently methylated in colorectal (CRC; 36 of 73 patients; 49%) and gastric (28 of 89 patients; 31%) cancer patients. Here, we show that DEXI methylation is implicated in mechanisms facilitating resistance to camptothecin (CPT) via inhibition of apoptosis. Silencing of DEXI by siRNA significantly reduced CPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…There are no identifiable domains in DEXI that might suggest a possible function for the protein. However, Miyaki et al ( 54 ) showed that small interfering RNA–mediated knockdown of DEXI reduced the incidence of apoptosis in cells treated with the chemotherapy agent camptothecin. A role in a basic cellular function, such as apoptosis, would be consistent with the involvement of DEXI in multiple autoimmune diseases with different target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There are no identifiable domains in DEXI that might suggest a possible function for the protein. However, Miyaki et al ( 54 ) showed that small interfering RNA–mediated knockdown of DEXI reduced the incidence of apoptosis in cells treated with the chemotherapy agent camptothecin. A role in a basic cellular function, such as apoptosis, would be consistent with the involvement of DEXI in multiple autoimmune diseases with different target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Bisulfite modification was performed using the Epitect Bisulfite kit (Qiagen), as described previously [36]. Genomic DNA (1 μg) was used for conversion with the bisulfite reagent.…”
Section: Methodsmentioning
confidence: 99%
“…DNA sequencing was performed after bisulfite modification, as previously described [36]. The primers for the bisulfite sequencing were 5′-TTGTATATAGTTTAGYGGTTGGG-3′ (forward) and 5′-AAATCTAAACTCCCTACACACTT -3′ (reverse).…”
Section: Methodsmentioning
confidence: 99%
“…Bcl-2/adenovirus E1B 19 kDa protein-interacting protein (BNIP3), a pro-apoptotic gene, was methylated in human colon cancer cell lines. BNIP3 upregulation led to the enhancement of irinotecan sensitivity [68,69] . Clinically, it has been suggested that BNIP3 methylation is associated with poor OS and shorter time to cancer progression [69] .…”
Section: Clinical Problems In Irinotecan-based Therapy and Overcoming Irinotecan Refractoriness Through Clinical Trials Including Dna Metmentioning
confidence: 99%